The efficacy and safety of immune combination therapy in patients with driver gene-negative non-small cell lung cancer with liver metastasis: a systematic review and network meta-analysis - Weixing Zhao; Bo Li; Yujia Gu; Xiaoni Jin; Zirui Li; Wanjing Guo; Xinxin Lu; Jun Jiang (BMC Cancer)
Abstract Objective This study aimed to systematically evaluate the efficacy and safety of combination therapies with immune checkpoint inhibitors (ICIs) in patients with driver gene-negative non-small cell lung cancer (NSCLC) and liver metastases. These patients typically have poor prognosis and limited responses to immunotherapy. This study synthesized existing literature by conducting a network meta-analysis to determine the most effective first-line ICI combination regimen to guide clinical treatment decisions. Methods We systematically searched the PubMed, Embase, Web of Science, and Cochrane Library databases for Phase III randomised controlled trials published up to 1 August 2024. Eligible studies underscored on patients with driver gene-negative NSCLC with liver metastases and reported progression-free survival (PFS), overall survival (OS), and treatment-related adverse events. Bayesian network meta-analysis was conducted using R (version 4.4.1) and STATA (version 17), with the results reported as hazard ratios (HRs) and 95% confidence intervals (CIs). Results Fourteen studies including 1,291 patients and 11 ICIs combination regimens were included. Pembrolizumab plus chemotherapy remarkably improved OS (HR, 0.64; 95% CI, 0.41–0.98). For PFS, tislelizumab plus chemotherapy (HR, 0.44; 95% CI, 0.26–0.74) and pembrolizumab plus chemotherapy (HR, 0.59; 95% CI, 0.39–0.90) were superior to other treatments. PD-1 inhibitors, such as pembrolizumab, combined with chemotherapy have shown greater efficacy than PD-L1 inhibitors, particularly for non-squamous cell carcinoma. High-grade adverse events, including hepatotoxicity, were more frequent in patients with liver metastases. Conclusion ICI-chemotherapy combinations offer a promising first-line treatment for driver gene-negative NSCLC with liver metastases. The pembrolizumab and tislelizumab combination demonstrated improved OS and PFS with distinct efficacy and safety profiles. Enhanced monitoring of liver function is recommended because of the risk of hepatotoxicity. Further studies are needed to confirm these findings and optimise individualised treatment strategies.